Job satisfaction application, assessment, cause, and consequences - Spector, Paul E. (SAGE, 1997)
This overview of the most studied variable in organizational behaviour research considers the nature of job satisfaction techniques for assessing job satisfaction, cultural and gender differences in job satisfaction, and more.- Resumé vydavatel
Keywords: pracovní spokojenost; job satisfaction; elektronické knihy; monografie; electronic books; monographs